ANALISIS PENGARUH PENGETAHUAN MENABUNG, BAGI HASIL DAN PERILAKU KONSUMEN TERHADAP KEPUTUSAN ANGGOTA MEMBUKA TABUNGAN SIMPANAN PELAJAR DI KSPPS MUI JATIM CABANG SEKAPUK - Rifqi, Mohammad; Harahap, Syamsir Alamsyah; Sahliyah, Fatihatus (Jurnal Ekonomi Syariah Darussalam, 2024)
This research aims to determine the influence of knowledge of saving, profit sharing, and consumer behavior on members' decisions to open student savings at KSPPS MUI Jatim Sekapuk Branch. The method used is a quantitative research method. The data collection technique uses a questionnaire with 20 items which are assessed using a 1-5 Likert scale and tested for validity and reliability. The data analysis technique to answer the hypothesis uses multiple linear regression analysis with correlation and determination coefficients, t test and f test. The results of multiple linear regression analysis from this research show that the calculated t value of the saving knowledge variable is 6,484 > 1.296, while the calculated t value of the profit sharing variable is 46,454 > 1.296 and the calculated t value of the consumer behavior variable is -4,365 < 1,296. This means that the savings knowledge and profit sharing variables partially influence members' decisions to open student savings savings at the KSPPS MUI East Java Sekapuk Branch, while the consumer behavior variables partially have no influence on members' decisions to open student savings savings at the KSPPS MUI East Java Sekapuk Branch. Meanwhile, the results of the F test show that the variables of knowledge of saving, profit sharing and consumer behavior simultaneously influence members' decisions to open student savings savings at KSPPS MUI Jatim Sekapuk Branch with F count 814.441>4.14 with a sig value of 0.000.